2019
DOI: 10.1002/soej.12365
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Treatment Effects of Participating Jointly in SNAP and WIC when the Treatment Is Validated Only for SNAP

Abstract: The U.S. Department of Agriculture operates several food assistance programs aimed at alleviating food insecurity. We study whether participation in both participation in both SNAP and WIC alleviates food insecurity compared with participation in SNAP alone. We bound underlying causal effects by applying nonparametric treatment effect methods that allow for endogenous selection and underreported program participation when validation data are available for one program (treatment) but not the other. We estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Other scholars have observed that simultaneous participation in federal nutrition programs, such as WIC and SNAP, is associated with lower risk of household food insecurity. (23) Differences in the implementation of these two programs, for example, in outreach activities or in the application process may explain varying coverage rates (defined as the percent of those eligible who are enrolled in the program).…”
Section: Discussionmentioning
confidence: 99%
“…Other scholars have observed that simultaneous participation in federal nutrition programs, such as WIC and SNAP, is associated with lower risk of household food insecurity. (23) Differences in the implementation of these two programs, for example, in outreach activities or in the application process may explain varying coverage rates (defined as the percent of those eligible who are enrolled in the program).…”
Section: Discussionmentioning
confidence: 99%
“…All consider the impact of SNAP, and several add analysis of the school meals programs or WIC. Jensen, Kreider, and Zhylyeskyy (2019) look at various assumptions about misreporting of WIC and SNAP together in a setting-FoodAPS-where only one program's self-reports are validated with administrative data. This extends other work by Brent Kreider and a host of other coauthors looking at set identification and bounding of causal effects in settings with endogenous selection and misclassification.…”
Section: Measurement Error and Effects Of Snap School Meals And Wicmentioning
confidence: 99%
“…A few studies conclude that SNAP participation alleviates food insecurity to some degree [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Although most existing studies use data from household surveys which are subject to reporting errors [ 20 , 21 ], a recent study suggests that the degree of reporting error is small and yields relatively little effect on the estimated impact of SNAP participation on food insecurity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%